2017
DOI: 10.3390/app7121276
|View full text |Cite
|
Sign up to set email alerts
|

High Power Fiber Laser Welding of Single Sided T-Joint on Shipbuilding Steel with Different Processing Setups

Abstract: Laser welding of thick plates in production environments is one of the main applications of high power lasers; however, the process has certain limitations. The small spot size of the focused beam produces welds with high depth-to-width aspect ratio but at times fails to provide sufficient reinforcement in certain applications because of poor gap bridging ability. The results of welding shipbuilding steel AH36 with thickness of 8 mm as a single-sided T-joint using a 10 kW fiber laser are presented and discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In this paper, a comprehensive overview on laser welding under vacuum is presented, which is a recently re-discovered laser welding technique [12] that can help in fully exploiting the potential of recently available high-power and high-brightness solid-state fiber and disk lasers. A study on high-power (10 kW) fiber laser welding of stainless steel T-joint focused on the investigation of the impact best fiber core diameter selection is presented by A. Unt, I. Poutiainen, S. Grunenwald, M. Sokolov, and A. Salminen in [13]. The effect of welding position on the quality of the laser welds is investigated in detail by B. Chang, Z. Yuan, H. Pu, H. Li, H. Cheng, D. Du, and J. Shan in [14], where a high-power (6 kW) fiber laser is used to weld titanium alloys.…”
Section: Solid State Lasers Materials Technologies and Applicationsmentioning
confidence: 99%
“…In this paper, a comprehensive overview on laser welding under vacuum is presented, which is a recently re-discovered laser welding technique [12] that can help in fully exploiting the potential of recently available high-power and high-brightness solid-state fiber and disk lasers. A study on high-power (10 kW) fiber laser welding of stainless steel T-joint focused on the investigation of the impact best fiber core diameter selection is presented by A. Unt, I. Poutiainen, S. Grunenwald, M. Sokolov, and A. Salminen in [13]. The effect of welding position on the quality of the laser welds is investigated in detail by B. Chang, Z. Yuan, H. Pu, H. Li, H. Cheng, D. Du, and J. Shan in [14], where a high-power (6 kW) fiber laser is used to weld titanium alloys.…”
Section: Solid State Lasers Materials Technologies and Applicationsmentioning
confidence: 99%
“…Laser welding has become an important method of marine steel plate joining because of the advantages of high-power density, low thermal distortion, rapid welding speed and so on. Unt et al [1] investigated laser welding of single sided T-joint on shipbuilding steel. It was reported that T-joints single-sided full penetration welding of AH36 with thickness of 8 mm were realized, possible cracks in fillet welds were avoided successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, low-heat input welding processes facilitate controlling the formation and growth of the IMC layer, leading to better mechanical performance. In this context, laser welding stands out as a very precise technique [17,18], which enables accurate control of heat input [19] and high cooling rates due to its very high energy density [20].…”
Section: Introductionmentioning
confidence: 99%